Capital Flows, Exchange Rate Flexibility, and the Real Exchange Rate - Combes, Jean-Louis.; Kinda, Tidiane; Plane, Patrick (Washington, D.C. : International Monetary Fund, 2011)
This paper analyzes the impact of capital inflows and exchange rate flexibility on the real exchange rate in developing countries based on panel cointegration techniques. The results show that public and private flows are associated with a real exchange rate appreciation. Among private flows, portfolio investment has the highest appreciation effect-almost seven times that of foreign direct investment or bank loans-and private transfers have the lowest effect. Using a de facto measure of exchange rate flexibility, we find that a more flexible exchange rate helps to dampen appreciation of the real exchange rate stemming from capital inflows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet